Digital Droplet PCR: CNV Analysis and Other Applications. (15th July 2014) - Mazaika, Erica; Homsy, Jason
ABSTRACT: Digital droplet PCR (ddPCR) is an assay that combines state‐of‐the‐art microfluidics technology with TaqMan‐based PCR to achieve precise target DNA quantification at high levels of sensitivity and specificity. Because quantification is achieved without the need for standard assays in an easy to interpret, unambiguous digital readout, ddPCR is far simpler, faster, and less error prone than real‐time qPCR. The basic protocol can be modified with minor adjustments to suit a wide range of applications, such as CNV analysis, rare variant detection, SNP genotyping, and transcript quantification. This unit describes the ddPCR workflow in detail for the Bio‐Rad QX100 system, but the theory and data interpretation are generalizable to any ddPCR system. Curr. Protoc. Hum. Genet . 82:7.24.1‐7.24.13. © 2014 by John Wiley & Sons, Inc.